Lean manufacturing - Michelle Talancon, Cecilia; López-Leyva, Josué Aarón; Chávez García, Dalia H.; Ponce Camacho, Miguel Ángel; Talamantes-Álvarez, Ariana (Intechopen, 2019)
In this chapter, several systems engineering tools are presented and analyzed to determine shortcomings of these tools to improve the efficiency and efficacy of them working together in a modified design thinking methodology framework for space systems management. The space systems projects impose a high risk in all its stages, so that it is very important to reduce errors as possible based on activities that ensure the adequate project performance. Finally, specific systems engineering tools are used in particular stages and sub-stages of the proposal design thinking framework depending on the shortcomings and strengths of each one. This proposal framework accelerates the conventional process for a space project that usually requires a lot of resources and it is not suitable for both emerging countries and space agencies.
A novel space systems management methodology based on shortcomings and strengths of conventional system engineering tools used in a design thinking framework
Keywords: Systems engineering tools; Design thinking; Space projects; Shortcomings-strengths; Efficiency; Sistemas